2009
DOI: 10.1182/blood-2008-09-179333
|View full text |Cite
|
Sign up to set email alerts
|

Severe bleeding complications caused by an autoantibody against the B subunit of plasma factor XIII: a novel form of acquired factor XIII deficiency

Abstract: Acquired factor XIII (FXIII) deficiency due to autoantibody against FXIII is a very rare severe hemorrhagic diathesis. Antibodies directed against the A subunit of FXIII, which interfere with different functions of FXIII, have been described. Here, for the first time, we report an autoantibody against the B subunit of FXIII (FXIII-B) that caused lifethreatening bleeding in a patient with systemic lupus erythematosus. FXIII activity, FXIII-A 2 B 2 complex, and individual FXIII subunits were undetectable in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 22 publications
1
85
0
Order By: Relevance
“…68 FXIII-B subunit deficiency results in loss of FXIII-A in plasma, presumed to be the result of instability, [69][70][71] but levels of platelet FXIII-A are normal. 70,72 FXIII-B deficiency is associated with milder symptoms than FXIII-A deficiency in humans 69 and FXIII-B knockout mice. 73 This is thought to be the result of the remaining levels of free FXIII-A in the plasma; however, our results suggest that platelet FXIII-A may also compensate under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…68 FXIII-B subunit deficiency results in loss of FXIII-A in plasma, presumed to be the result of instability, [69][70][71] but levels of platelet FXIII-A are normal. 70,72 FXIII-B deficiency is associated with milder symptoms than FXIII-A deficiency in humans 69 and FXIII-B knockout mice. 73 This is thought to be the result of the remaining levels of free FXIII-A in the plasma; however, our results suggest that platelet FXIII-A may also compensate under these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In a most recent Japanese study, 11 patients with nonneutralizing anti-FXIII-A autoantibodies were reported as opposed to five with neutralizing antibodies [24 ]. An autoantibody against FXIII-B was first reported in 2009 [28]. It formed a complex with FXIII-B and FXIII-A 2 B 2 and highly accelerated their clearance from the circulation causing life-threatening bleeding complications.…”
Section: Classification Of Fxiii Deficienciesmentioning
confidence: 99%
“…Demonstration of the binding of the patient's IgG (IgM) to isolated FXIII subunits and FXIII complex in an ELISA or dot blot arrangement is required to diagnose the presence of a nonneutralizing anti-FXIII autoantibody [24 ,28]. To verify the accelerated clearance of FXIII from the circulation, the decrease of FXIII activity/antigen is to be followed by serial measurements following supplementation [27,28]. An example for the diagnosis of nonneutralizing autoantibody is shown in Fig.…”
Section: If Autoantibody Is Suspectedmentioning
confidence: 99%
“…However, we were not able to use rituximab in this case because its use for this disorder is not currently accepted at our hospital. In other previously studies in which steroids, CPA, and CyA were ineffective (11,12), alternative treatments, such as plasmapheresis, immunoglobulin, and rituximab, were used, resulting in increased FXIII activity. In the present case, active bleeding has not recurred since the patient began PSL treatment, which represents clinical remission.…”
Section: Discussionmentioning
confidence: 99%